THE EFFECT OF INFLATION LEVELS AND OIL PRICES ON STOCK RETURN FOOD AND BEVERAGE - Kristian Chandra (Business and Entrepreneurial Review, 2017)
This study aims to synthesize to see the consequences of inflation and oil prices on stock returns. The shares observed in this study are stocks that are included in the food and beverage section listed on the Indonesia Stock Exchange (IDX) during the year 2010-2015. To determine the sample sorted in this study is to use Purposive Sampling techniques to obtain samples that match the parameters that have been used as a benchmark. The number of food and beverage industry samples that meet the criteria are 13 listed on the Indonesia Stock Exchange in 2010-2015. Regression analysis using the EViews program was chosen as the method used in analyzing the data. The results confirm that inflation has a negative and significant effect on stock returns and oil prices have a positive and significant effect on the return of food and beverage stocks listed on the IDX in 2010-2015.